Public finance and public investments in the context of intensification of economic development. - Ivashko, Olena (Волинський національний університет імені Лесі Українки, 2024)
The purpose of this article is to study the interdependence of the state, local governments, institutional investors and the level of foreign direct investment in Ukraine's economy in conditions of instability. The article examines the role of institutional investors and clarifies the main trends in attracting investment resources into the economy of Ukraine, taking into account the European integration vector, the state investment policy of Ukraine should include the main aspects of the main goals and objectives of the new generation investment policy, which takes into account the latest trends and needs of the world economy. In this context, it is especially important to establish the optimal ratio of foreign direct and domestic investment. In the context of European integration processes and ensuring investment security in Ukraine, it is necessary to protect domestic markets from monopolization by foreign investors by setting a limit on foreign direct investment in each sector.
Keywords: finance; public finance; investment; investment activity; investment climate; state; 336.1